The Relationship Between the Implementation of Room Head Management and the Work Motivation of Implementing Nurses in the Inpatient Ward of A. Makkasau Parepare Regional Hospital - Vonny, Vonny; Rais, Muh Kardi; Ali, Muh Yamin; Hasbullah, Hasbullah; Irawan, Mady (Journal of Community Health Provision, 2024)
Motivation is all things verbal, physical, or psychological that make someone do something in response. The provision of maximum health services in hospitals can be achieved if the work motivation of nurses is high. The purpose of this study was to determine the relationship between discipline, effective communication and assertiveness training with the work motivation of implementing nurses in the inpatient ward of A. Makksau Parepare Hospital in 2022. The type of research used is a descriptive approach method using a Cross Sectional Study design. The population in this study were nurses in the inpatient room of A. Makkasau Parepare Hospital who had been registered as civil servants as many as 115 people. The sample in this study was 53 respondents with a sampling technique of purposive random sampling . Data collection was carried out using a questionnaire. The results of the study showed that there was a relationship between discipline (p=0.013) and the work motivation of implementing nurses, there was a relationship between effective communication (p=0.020) and the work motivation of implementing nurses, there was a relationship between assertive training (p=0.014) and the work motivation of implementing nurses. The conclusion and suggestion in this study is that there is a relationship between discipline, effective communication, assertive training with the work motivation of implementing nurses, and it is suggested for the head of the room to further improve the work motivation of implementing nurses and for further researchers to be able to conduct further research on the relationship between discipline, effective communication, assertive training with the work motivation of implementing nurses.